Automatic Water Level and Pressure Control System Prototype Design Using Programmable Logic Controller and Human Machine Interface - Hajar, Ibnu; Damiri, Dhami Johar; Sitorus, Meyharth Torsna Bangkit (International Journal of Advanced Science Computing and Engineering, 2023)
Water level control and pressure control are implemented in many at several industrial processing such as water dam, petrochemical processing plant, pharmacy and food processing plant, overhead tank, waste processing plant, electricity plant, etc. This study analyses a simulation and a needed components for automatically water level control system implementation using programmable logic controller (PLC). The water level control using PLC is designed to control the water level and prevent waste the water from a water tank. PLC is one of devices of automated controller which mostly used. Use of PLCs in industries are indispensable to control parameters which required high precision. In this research studies water level control system using PLC as primary controller and human machine interface (HMI) as remote controller that could visualize state of a system work (plant) in real time on computer screen and could gather field data as well. Main device for this research is Omron PLC CP2E type and touchscreen HMI Omron. At the prototype is used a water tank and a water container (to be one with the water resource), and in the HMI is showed the pages of home, control panel, and plant. From the result of the diagram ladder and the HMI design are got the system run well. The application from this research could be learning media in the system control laboratory for the subject of industrial control system and the others, related to it.